ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Futri, Amelia; Shinta, Renea; Dali, Rahmat Mulyana (STIE Perbankan Indonesia, 2024)
Entering This research aims to analyze and determine the influence of dividend policy, funding decisions and interest rates on firm value. The population used in this research were 22 companies in the telecommunications subsector listed on the IDX for the 2017-2023 period. The sample was taken using purposive sampling and 5 companies were obtained. The method used in this research is a quantitative method with data analysis techniques using panel data regression. Based on the results obtained, it shows that partially dividend policy has no significant effect on firm value, funding decisions have a significant effect on firm value, interest rates have no significant effect on firm value, and simultaneously dividend policy, funding decisions and interest rates have a significant effect on firm value. Keywords: Dividend Policy, Funding Desicious, Firm Value, Interest Rate.